A rare presentation of dengue fever: acute motor quadriparesis due to hypokalemia - Singh, Jitendra; Singh, Ambukeshwar; Dinkar, Anju; Atam, Virendra (International Journal of Research in Medical Sciences, 2017)
Hypokalemia can lead to acute onset pure motor flaccid quadriparesis. Although there are many causes of hypokalemia but dengue is a one rare cause of them which can cause hypokalemia. Simply correction of potassium improve the weakness dramatically. We reported a case who presented to us with acute motor quadriparesis, finally diagnosed hypokalemia due to dengue.